SARS-CoV-2 infection of human pluripotent stem cell-derived vascular cells reveals smooth muscle cells as key mediators of vascular pathology during infection - Alexsia Richards; Andrew S. Khalil; Max Friesen; Troy W. Whitfield; Xinlei Gao; Tenzin Lungjangwa; Roger D. Kamm; Zhengpeng Wan; Lee Gehrke; David Mooney; Rudolf Jaenisch (Nature Communications)
Abstract Although respiratory symptoms are the most prevalent disease manifestation of infection by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), nearly 20% of hospitalized patients are at risk for thromboembolic events. This prothrombotic state is considered a key factor in the increased risk of stroke, which is observed clinically during both acute infection and long after symptoms clear. Here, we develop a model of SARS-CoV-2 infection using human-induced pluripotent stem cell-derived endothelial cells (ECs), pericytes (PCs), and smooth muscle cells (SMCs) to recapitulate the vascular pathology associated with SARS-CoV-2 exposure. Our results demonstrate that perivascular cells, particularly SMCs, are a susceptible vascular target for SARS-CoV-2 infection. Utilizing RNA sequencing, we characterize the transcriptomic changes accompanying SARS-CoV-2 infection of SMCs, PCs, and ECs. We observe that infected SMCs shift to a pro-inflammatory state and increase the expression of key mediators of the coagulation cascade. Further, we show human ECs exposed to the secretome of infected SMCs produce hemostatic factors that contribute to vascular dysfunction despite not being susceptible to direct infection. The findings here recapitulate observations from patient sera in human COVID-19 patients and provide mechanistic insight into the unique vascular implications of SARS-CoV-2 infection at a cellular level.